Thermal stability of phosphate coatings on steel - P. Pokorny; P. Szelag; M. Novak; L. Mastny; V. Brozek (Metalurgija, 2015)
The work was validated thermal stability of zinc, manganese and tri-cations phosphate coatings on steel, made from commercial phosphating bath type Pragofos. Thermogravimetric data dehydration of scholzite, phosphophylite and hureaulite coatings in the temperature range 160 °C – 400 °C define the conditions for applying paints with higher firing temperature or thermal spraying ceramic coatings.